Sartorial disruption: an investigation of the histories, dispositions, and related museum practices of the dress/fashion collections at Iziko Museums as a means to re-imagine and re-frame the sartorial in the museum - de Greef, Erica (African Studies, 2019)
In this thesis I investigate and interrogate the historical and current compositions, conditions and dispositions of three collections containing sartorial objects of three formerly separate museums – the South African Museum, the South African National Gallery and the South African Cultural History Museum. Although these three museums were amalgamated in 1999, along with eight other Western Cape institutions to form Iziko Museums, each separate sartorial ‘collection’ retains the effects of the divergent museal practices imposed on its objects over time. I employ the concept of ‘fashion’ in this thesis both to refer to the objects of the study, as well as to the socially-determined set of ideas and ideals surrounding notions such as taste, aesthetics, belonging and modernity. Sartorial objects in museums present strong physical evidence of both deeply personal and extremely public relationships as the traces of and capacity for embodiment imbue these objects with metonymic, subjective and archival capacities. In addition, I employ the contracted form dress/fashion to trouble the commonly held separate notions of ‘fashion’ as a modern, dynamic and largely Western system, and ‘dress’ as ‘traditional’ and an unchanging African sartoriality. I contend that through the terms ‘dress’ and ‘fashion’ – two opposing and segregating tropes still largely present in South African museums – the forms of agency, mutability and historicity applied to Western ‘fashion’ objects, have been and continue to be denied in the collection, classification and curation of African ‘dress’. I use a sartorial focus to unpack the development of and conditions pertaining to each of the museums in this study, namely an ethnographic museum, a cultural history museum and a fine arts museum. I interrogate the three separate phases of dress/fashion objects in these museums, that is, their entry into the collections, their classification and their display. Following each historical investigation, I use a single object-focused strategy to reflect on the specific conditions, dispositions and limitations of these three separate sartorial ‘archives’. I choose to identify and analyse all the trousers found across the three collections (as well as some significant examples that were excluded), as these particular sartorial objects both reflect and offer critical insights into distinct, and often divisive, definitions of gender, politics and socio-cultural attitudes, many of which also changed over time. I offer close readings of a number of trousers (both in and absent from these collections) that make evident the ways in which these divisions have been scripted into the taxonomies, disciplines and exhibitions at Iziko Museums. These practical and conceptual divisions perpetuate the artificial segregation of these museum objects. The divisions are also reflective of wider divisive museal practices that persist despite the efforts of Iziko Museums to transform and integrate their practices and their collections. Drawing on the sartorial as an alternative archive I am able to show the types of histories avowed and disavowed by different museal practices. In addition, the close readings expose the distinct and persistent colonial and apartheid underpinnings of sartorial classification and representation across the three Iziko Museums’ collections almost twenty years after the merger. The trousers readings furthermore, make a number of decolonial affordances evident, as the objects reflect not only alternate histories, but also shared pasts prompting alternative contemporary interpretations. Via the dress/fashion collections, this thesis offers a sartorial approach to ‘decolonising’ the museum. This includes both a reframing of various museal practices and principles, and a contemporary re-imagining of histories and their related identity narratives. Despite contemporary critiques and attempts to transform the disciplinary practices, and various cultural and social distinctions still present in the collections and exhibitions at Iziko Museums, segregation and problematic hierarchies still persist. I show how when considered as an archive, the sartorial makes evident other histories, relationships and interpretations. This approach can contribute towards a new, interdisciplinary dress/fashion museology as both a means of disruption and revision at Iziko Museums, contributing towards new contemporary capacities to curate the sartorial offering alternate, decolonial interpretations of past, present and future South African identity narratives.